Evaluation of the microbiological and physical-chemical quality of salted bovine meat marketed in establishments and free fairs in the north zone of Rio de Janeiro - Julio Cesar Queiroz Penha; Robson Maia Franco; Maria Carmela Kasnowski Holanda Duarte; Katia Christina Leandro (Fundação Oswaldo Cruz (FIOCRUZ), 2018)
Introduction: Salted beef is a highly handled product that can be contaminated by pathogenic microorganisms and foreign materials. Objective: Evaluate the microbiological and physicalchemical quality of charque and jerked beef. Method: Thirty samples were evaluated by microbiological research and count, physical-chemical analysis and microscopical research. Results: Halophilic bacteria count ranged from 5.2 to 8.8 log CFU/g, molds and yeasts from 2.8 to 8.2 log CFU/g. Although high results have been observed, there are not tolerance limits for these microorganisms in legislation. Staphylococcus spp. count ranged from < 2.0 to 7.8 log CFU/g, coliforms at 45°C from < 3.0 to 9.3 x 102 MPN/g, beyond the absence of Salmonella spp. These results showed 11 samples above the limit for Staphylococcus coagulase positive and all samples were lower than the recommended for coliforms at 45ºC. In the physicalchemical analysis, seven charque samples were observed above the limit recommended for the residual moisture content. In the analysis of fixed mineral residue, 18 charque samples and one of jerked beef were also above the limit. In the microscopical research, mites and furs were observed in three charque samples. Conclusions: Results showed the necessity of more effective hygienic-sanitary practices in the manipulation of these products.